Comparison of the clinical efficacy and safety of two spinal endoscopic techniques for the treatment of ossification of the ligamentum flavum in the thoracic spine - Yupeng Wang; Zhongxin Tang; Qian Tang; Haijun Ma; Mingkui Shen; Hejun Yang (Frontiers in Neurology)
PurposeThe purpose of this study was to compare the clinical efficacy and safety of the percutaneous endoscopic (PE) technique and the unilateral biportal endoscopic (UBE) technique for the treatment of thoracic ossification of the ligamentum flavum (T-OLF).MethodsThis study retrospectively analyzed T-OLF patients who received endoscopic surgical treatment from January 1, 2020, to December 31, 2022. Patients were divided into a PE group and a UBE group according to the surgical method. The basic information of the patients was recorded. Preoperative and postoperative neurological status was evaluated using the mJOA score, American Spinal Injury Association (ASIA) sense score (ASS), and ASIA motor score of the lower extremities (AMS). The mJOA recovery rate (RR) was also calculated. T-OLF can be diagnosed on the basis of sagittal Magnetic Resonance Imaging (MRI) and axial Computed Tomography (CT).ResultsA total of 64 patients were followed for an average of 12–24 months. 33 patients underwent UBE surgery, and 31 patients underwent PE surgery. There was no significant difference in baseline characteristics between the two groups (p > 0.05). Neurological function was significantly improved in both groups after surgery. Compared with the PE group, the UBE group experienced better postoperative clinical efficacy, and the difference was statistically significant (p < 0.05). Postoperative CT and MRI revealed that the degree of spinal cord compression in patients in the UBE and PE groups was relieved. 4 patients in the PE group and 1 patient in the UBE group had dural sac tears. 3 patients with upper thoracic vertebrae in the PE group exhibited transient neurological deficits. These complications did not cause serious consequences.ConclusionFor patients with T-OLF, both UBE and PE can effectively alleviate nerve compression and relieve symptoms. UBE uses two channels for observation and operation, leading to more effective and safer clinical outcomes.